Let's simplify and solve the equation step by step:
-
Start with the original equation:
\[ 3x - \frac{1}{5} - \frac{2}{9}x = \frac{124}{5} \]
-
Combine like terms. The terms containing \(x\) are \(3x\) and \(-\frac{2}{9}x\). To combine these, we need a common denominator. The least common multiple of the denominators \(1\) and \(9\) is \(9\):
\[ 3x = \frac{27}{9}x \]
Now we can combine:
\[ \frac{27}{9}x - \frac{2}{9}x = \frac{27 - 2}{9}x = \frac{25}{9}x \]
So, we can rewrite the equation as:
\[ \frac{25}{9}x - \frac{1}{5} = \frac{124}{5} \]
-
Next, let's isolate the variable term by adding \(\frac{1}{5}\) to both sides:
\[ \frac{25}{9}x = \frac{124}{5} + \frac{1}{5} \]
\[ \frac{25}{9}x = \frac{124 + 1}{5} = \frac{125}{5} = 25 \]
-
Now, to isolate \(x\), we multiply both sides of the equation by the reciprocal of \(\frac{25}{9}\), which is \(\frac{9}{25}\):
\[ x = 25 \cdot \frac{9}{25} \]
\[ x = 9 \]
So the solution to the equation is:
\[ \boxed{9} \]